Effect of adding different silane coupling agents on metal friction and wear in mixing process. Issue 47 (29th July 2021) - Han, Deshang; Pan, Yi; Xue, Junxiu; Yu, Benhui; Yan, Gang; Wang, Chuansheng; Wang, Kongshuo; Pan, Yiren
Abstract: The function of silane coupling agent in rubber mixing field is to combine inorganic matrix with rubber organic matrix. Silica is commonly used in the rubber mixing field to strengthen rubber. The size and amount of silica aggregates in the mixing process are important factors affecting the wear of the mixing chamber. The wear of the mixing chamber would lead to a increasing gap between the mixer chamber and the rotor, which caused the mixing efficiency reducing. It also affected the dispersion effect, then affected the mechanical and physical properties of the vulcanized rubber. In this paper, the effects of rubber compound on metal friction and wear were studied by using four silane coupling agents commonly used in rubber mixing field. The experiment was carried out at 15°C, and the attention should be paid to drying during sample preparation to avoid the deviation of the experiment caused by hydrolysis of silane coupling agent. The results showed that silanization reaction occured between silica and silane coupling agent in the mixing process. The mixing temperature was usually maintained at 145 to 155°C for 1 min in the mixer, and the silanization reaction rate was the fastest during this time. We took this rubber compound as the research object and studied the friction and wear of the rubber compound on the mixing chamber in the mixing process. The products of the silylation reaction are alcohol and water. This paper studies the corrosion and abrasion of the mixing chamber by water at high temperatures. In the mixing process, abrasive wear was the main wear form, but the corrosion wear caused by high temperature steam still occupied a large proportion. Abstract : In this paper, the effects of rubber compound on metal friction and wear were studied by using four silane coupling agents commonly used in rubber mixing field. This paper studies the corrosion and abrasion of the mixing chamber by water at high temperatures. In the mixing process, abrasive wear was the main wear form, but the corrosion wear caused by high temperature steam still occupied a large proportion.